2012
DOI: 10.1007/s00436-012-2864-3
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of Plasmodium vivax thioredoxin peroxidase-1

Abstract: Reactive oxygen species produced from hemoglobin digestion and the host immune system could have adverse effects on malaria parasites. To protect themselves, malaria parasites are highly dependent on the antioxidant enzymes, including superoxide dismutases and thioredoxin-dependent peroxidases. To date, several thioredoxin peroxidases (TPx) have been characterized in Plasmodium falciparum, but the TPx in Plasmodium vivax has not yet been characterized. The complete sequence of gene coding for thioredoxin perox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 18 publications
2
16
0
Order By: Relevance
“…3B, BgTPx-1 was observed around the nucleus of the parasite. This cytoplasmic expression pattern was also shown in typical 2-Cys peroxiredoxins of P. falciparum (PfTPx-1) [31], P. vivax (PvTPx-1) [11] and B. bovis (BbTPx-1) [27]. Recently, our group showed that BbTpx-1 gene disruption does not affect in vitro intraerythrocytic growth of B. bovis [2], as previously reported for the gene disrupted in P. berghei [30], indicating that the TPx-1 gene is not essential for the erythrocytic stage of Babesia parasites.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…3B, BgTPx-1 was observed around the nucleus of the parasite. This cytoplasmic expression pattern was also shown in typical 2-Cys peroxiredoxins of P. falciparum (PfTPx-1) [31], P. vivax (PvTPx-1) [11] and B. bovis (BbTPx-1) [27]. Recently, our group showed that BbTpx-1 gene disruption does not affect in vitro intraerythrocytic growth of B. bovis [2], as previously reported for the gene disrupted in P. berghei [30], indicating that the TPx-1 gene is not essential for the erythrocytic stage of Babesia parasites.…”
mentioning
confidence: 76%
“…Since 2-Cys Prxs use electrons provided by the small protein thioredoxin, these enzymes are also called thioredoxin peroxidases (TPx) [15, 19]. In recent years, several Prxs of malaria parasites have been characterized, and the structural and functional properties of the enzymes have been determined as key factors for development of new drugs [3, 11, 13, 16, 21]. Recently, a Prx from the bovine Babesia parasite B. bovis (BbTPx-1) was identified, and its antioxidant activity was demonstrated [27].…”
mentioning
confidence: 99%
“…Therefore, it is thought to be the principal enzyme for the removal of excessive H 2 O 2 and to protect living organisms from such oxidative damages [51]. Moreover, peroxiredoxin also plays a key role in tumor suppression, immune response, signal transduction, as well as maintaining redox homeostasis [52,53,54,55,56,57,58]. Peroxiredoxins do not contain tightly bound metal ions, like other well-known antioxidant enzymes, but they contain highly conserved redox-active cysteine, which is involved in the catalytic mechanism [59].…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant proteins were produced as described previously [12, 13]. Briefly, the PCR products were digested with restriction enzymes (Supplementary Table S1) and then inserted into pET-28a expression vector (EMD Biosciences, San Diego, CA) by overnight incubation with ligation mixture (Takara, Otsu, Japan) at 15°C.…”
Section: Methodsmentioning
confidence: 99%